An empirical study on the moderating effect of environmental audit on the impact of economic development and ecological environment - Xiong, Mingliang (Frontiers in Psychology, 2022)
Environmental audit is a new thing. As an important part of national audit, it is an important environmental governance supervision and control mechanism in China, but what is the macro environmental governance effect of environmental audit? Can environmental audit promote regional pollution control? Does environmental audit play a role in regulating the effect of environmental pollution control on the basis of economic development? The research on these issues has great practical and theoretical significance. Through questionnaire, 217 valid data were finally obtained as research samples. Using correlation analysis, partial correlation analysis, full regression, and stepwise regression analysis, on the basis of testing the explanatory power of economic development and environmental audit on ecological environment quality, the paper further tested the impact of the interactive multiplier of environmental audit and economic development on ecological environment quality. The study found that: not only do economic development and environmental auditing each have a significant positive correlation on the quality of the ecological environment; moreover, economic development and environmental auditing interact with each other to influence the ecological environment, and the degree of correlation and influence of environmental auditing on the ecological environment is greater than the degree of correlation and influence of economic development on the ecological environment. Environmental auditing has a significant positive moderating effect on economic development in the process of improving ecological and environmental quality, and on the basis of economic development, environmental auditing by the government has a more significant effect on the improvement of ecological and environmental quality. Studying this problem is not only conducive to guiding the government audit department to take on the role in the ecological environment governance, but also to more effectively control the environmental pollution problem, realizing the cooperation and mutual penetration of the role of government environmental audit in economic development and ecological environment protection policies. It provides reference for future empirical research using micro survey data, and also provides policy suggestions for economic construction, environmental audit, and ecological environment governance in various regions of China, and provides empirical evidence support for contingency theory.